Expression and localization of IL-1β mRNA is interrelated with cytoskeletal rearrangement in monocytes stimulated by adherence: a light microscopy in situ hybridization study - Böcker, Ulrich; Sirenko, O. I.; Morris, J. S.; Sartor, R. B.; Singer, Manfred V.; Haskill, J. S.; Watson, J. M. (Immunology & cell biology, 2001)
Differences in IL-1β mRNA expression, stability and translation between non-adherent monocytes and those stimulated by adherence suggest that cytokine regulation is coupled to the function and assembly of cytoskeletal structures. In situ hybridization studies were performed to visualize expression and positioning of IL-1β mRNA in adherently cultivated monocytes. IL-1β mRNA expression was heterogeneous with high transcript levels found in spread or polarized cells. Transcripts were compartmentalized to the perinuclear region in spread cells, and partially redistributed with polarization. In contrast to mRNA distribution in other motile cell populations, IL-1β mRNA did not localize to the distal or proximal actin cytoskeleton. Perinuclear confinement of transcripts required intact actin microfilaments. Treatment with cytoskeleton disruption and detergent extraction suggested that most non-translated IL-1β mRNA was associated with intermediate filaments. In monocytes stimulated by LPS, IL-1β, but not IL-1Ra transcripts were redistributed and partially associated, yet not bound to actin microfilaments. The present study demonstrates that IL-1β mRNA expression and localization in adherent monocytes is interrelated with the cytoskeletal rearrangement upon adherence, spreading and polarization.
Gesehen am 29.04.2022